Why is School-University-Industrial Partnership Management Relevant in 21st Century Education? - Harjono Harjono; Heri Yanto; Sri Susilogati; Budiyono Budiyono (International Conference on Science, Education, and Technology, 2021)
This study aimed to analyze the relevance of School–University–Industry Partnership Manage-ment (SUIPM) in improving students’ employability skills. The study addresses two research questions: How can students’ employability skills be strengthened through SUIPM?; and How can teachers appreciate the SUIPM to strengthen students’ employability skills? This research used a qualitative methodology conducted with a survey. The research participants were twen-ty-seven industrial chemistry teachers in Central Java, Indonesia. Data were collected in two ways: through interviews and questionnaires with Google Forms. The collected data were ana-lyzed using an interactive model. The results showed that the SUIPM is a feasible strategy to be implemented to strengthen students’ employability skills. The teachers provided positive appreciation for the SUIPM, considering it as a trigger for strengthening students’ employability skills. The results also provide feedback on the “teaching factory”—a program initiated by the government—which so far has not had an optimal impact in preparing prospective skilled workers.